Parallel reaction monitoring to improve the detection performance of carcinogenic 4-methylimidazole in food by liquid chromatography-high resolution mass spectrometry coupled with dispersive micro solid-phase extraction. (June 2018) - Chen, Dawei; Yan, Pengcheng; Lv, Bing; Zhao, Yunfeng; Wu, Yongning
Abstract: Carcinogenic 4-methylimidazole (4-MEI) formed by Maillard reaction is commonly found in various food, which are colored with caramel or prepared in cooking and roasting processes. The sample preparation and detection of 4-MEI are extremely difficult due to its low molecular weight and high water solubility. In this study, a simple sample preparation based on the dispersive micro solid-phase extraction (dispersive micro SPE) procedure was developed for the analysis of 4-MEI in food. Dispersive micro SPE method is convenient, time-saving and low-cost, and its cleanup effect is comparable to that of the traditional SPE method. Moreover, liquid chromatography-high resolution mass spectrometry (LC-HRMS) was also used for the accurate qualitative and quantitative detection of 4-MEI. Among various acquisition modes of HRMS, a new parallel reaction monitoring (PRM) mode was found to contribute to a significant reduction in background noise of 4-MEI, resulting in its detection performance increased by 50- or 100-fold. Finally, this method was validated in eight kinds of food, including the complex matrices (soy sauce, vinegar, coffee and tea), and applied in real food samples. The results showed that the presence of 4-MEI in cooking and roasting food (e.g. coffee and tea) is of concern. Highlights: Dispersive micro SPE method for replacing the traditional SPE method were established. The detection performance of 4-MEI was improved and increased by 100-fold. The matrix effect of this method was evaluated in various food. The method validation was conducted in various food, including liquid and solid samples. The presence of 4-MEI in cooking and roasting food (e.g. coffee and tea) is of concern.